A COMPREHENSIVE REVIEW OF WORK-FAMILY BALANCE THEORIES - Ugo Chuks Okolie; Onofere Princewill OKEREKA (Universitas Kuningan, 2022)
This study offers a thorough analysis of work-family balance theories. Secondary data from books and published articles were used in the investigation. There is no widely acknowledged central paradigm for work-family balance, according to the paper's conclusion. The breadth of the study's framework, variables, or perspectives affects the theories utilized by academics in the subject of work-family balance, which can lead to omissions or overlap in frameworks or constructions. The segmentation, resources, spillover, resource drain, integration, border, and enrichment theories, among others with acceptable descriptions, are the key conceptual frameworks relevant to the work and family domains that are included in this research.